FOXP3 immunohistochemistry on formalin-fixed paraffin-embedded tissue: poor correlation between different antibodies. Issue 8 (15th April 2008) - Woo, Y L; Sterling, J; Crawford, R; van der Burg, S H; Coleman, N; Stanley, M
Abstract : Since its original description, there has been a substantial output of publications related to the FOXP3 gene. The FOXP3 protein, a member of the forkhead/winged-helix family of transcriptional regulators is a nuclear product and is not expressed in the cell cytoplasm or on the cell surface. Expression of this single transcription factor causes a developmental switch in naïve T cells to a suppressor cell phenotype, more commonly referred to as regulatory T cells (Tregs). Tregs have been intensively studied in various autoimmune diseases, infections and different cancers. An increasing choice of commercially available monoclonal antibodies targeting FOXP3 is now available. This report describes the experience of using two commonly used monoclonal FOXP3 antibodies on formalin-fixed paraffin-embedded sections of different organs, including the cervix and vulva. The antibodies targeting different FOXP3 epitopes unexpectedly resulted in significantly different staining patterns. This phenomenon has not been previously reported and is likely to be an important observation.